Penilaian Kandang Sehat dan Produktif Domba di Desa/Kelurahan Lingkar Kampus Institut Pertanian Bogor, Darmaga - Rahmat Hidayat; Kukuh Santoso; . Suryahadi; Sri Darwati; Agik Suprayogi; . Prastowo (Institut Pertanian Bogor, 2015)
Institute for Research and Community Service Bogor Agricultural University (LPPM IPB) has excellent performance in community service activities (PPM). LPPM IPB since 2009 has conducted various community service activities in rural and urban campus area around of Campus. One of the activities is related with sheep and supporting activities. This assessment activity has two (2) purposes: first, to measure the knowledge of farmers in the application of science and technology especially cage and cultivation that has been given, and the second one, to give appreciation for the achievements of farmers in the management of sheep, especially for the category of healthy and productive cage. This activity was carried out by field visits and interviews using a special form of assessment. 17 breeders were determined based on nonprobability purposive sampling method. The highest value obtained Nurpandi farmer from the Village Sukawening got 920.9 points, while the lowest value obtained Sahedi farmer from the Village Purwasari got 308.3 points. Conclusions from the results obtained showed mostly cage sheep (52.94%) have not yet reached the category of healthy and productive cage (final value of less than 800 points).